IDENTIFIKASI DAN UJI FITOREMEDIASI BEBERAPA TUMBUHAN AIR ASAL KOLONG PASCA PENAMBANGAN TIMAH - IDHA SUSANTI; SITI AMINAH; MUNAWAR MUNAWAR (Akuatik: Jurnal Sumberdaya Perairan, 2013)
Phytoremediation, an emerging cleanup technology for contaminated soils, groundwater, and wastewater that is both low-tech and low-cost to remove, contain, or render harmless such environmental contaminants as heavy metals, trace elements, organic compounds, and radioactive compounds in soil or water. Bangka Island has some environmental problem that caused tin mining activities. One of them is the formation of pits that have an impact on the carrying capacity of land resources and environmental quality. The aims of research were to identify some native aquatic plants from tin-mined pit and to test some selectable native aquatic plants for bioremediation on medium treatment. Bioremediation tested have been done using 4 selectable plants on 5 combinations of water and medium treatment. The experiment is conducted with 4x5 designs of random factorial pattern and three replications. The measured parameters were: contents of heavy metal (Pb, Cu, Zn) of water, plant canopy and root; fresh weight ratio of the root/canopy, total fresh weight plant; total dry weight plant; DO; and pH. Field surveys in several districts of Bangka (Pemali and Riding Panjang) found some potential aquatic plants for phytoremediation. There were 14 species from 11 genuses. Most of them were Cyperacea. They were species in Pemali and Riding Panjang pit ponds. The selectable plants which used for phytoremediation test were E. ochrostachys, L. articulata, S. cucullata, dan T. angustifolia The phytoremediation treatment showed 4 aquatic plants had good potential for phytoremediation. Based on the heavy metals measurements of Pb, Cu, and Zn, L. articulata was the best plant to accumulate Pb metal (317,35 ppm), and T. angustifolia was the best plant to accumulate Cu and Zn metals (43,55 and 167,25 ppm). Both were phytoaccumulation plants and using phytoextraction mechanism. The selectable plants could increase the DO value and pH rising on the medium treatment